IMPACT OF CORONAVIRUS DISEASE (COVID-19) ON PUBLIC ARCHIVES IN MALAYSIA - Ahmad Azman Bin Mohamad Ramli; Norhidayu Binti Md Yatim; Noor Faraliza Binti Samsudin; Nor Zaina Zaharah Binti Mohd Ariff; Kasmarini Binti Baharuddin; Mohd Naim Bin Mohd Nasfi (International Journal of Accounting, Finance and Business, 2022)
The emergence of Covid-19 has had an impact on various aspects of human life inthe world and Malaysia is no exception to this situation. In this regard, the objective of thisstudy is to make a survey to determine the impact of the emergence of the disease to the publicarchives in Malaysia. It is hoped that knowing the impact, it can make the parties responsiblefor managing public archives in Malaysia and the Malaysian community in general moreprepared to face any emergence of infectious diseases that risk disrupting the smoothmanagement of this invaluable national treasure. To achieve the objectives of the study,researchers use the approach of literature review (literature review) to obtain informationrelated to the topic of study. Reference media such as newspapers, books, social media such asFacebook, websites and so on are used. The results of the study found that there are certainimpacts on public archives in Malaysia because of the emergence of this disease in Malaysia.These impacts are described one by one in this article. It is hoped that the results of this studywill be a catalyst for researchers to conduct research on this issue in more depth in the futureto help ensure that public archives in Malaysia can continue to be preserved and can be usedfor current and future generations.